Socio-Demographic Factors Associated With Choice Of Place Of Delivery Among Women Attending Antenatal Care At Tassia Kwa Ndege Hospital Embakasi East, Nairobi Kenya - Momanyi, Vincent; Nyongesa, Margaret Wandera; Okeyo, Isaac (IOSR Journal Of Humanities And Social Science, 2025)
are made to increase access to quality maternal health care. Nairobi County constructed new hospitals within densely populated areas to bridge the gap to healthcare access and reduce the strain on the already existing health facilities that are overcrowded. Tassia kwa Ndege Hospital in Embakasi East Constituency was one of the new hospitals constructed to address this gap. Material and methods: A cross-sectional study design was adopted utilizing quantitative data collection methods. The sample comprised 290 respondents selected through systematic random sampling from those who were seeking antenatal care services at Tassia kwa Ndege hospital. Data was analyzed using SPSS, with descriptive statistics and Chi-tests employed to establish association socio-demographic factors associated with the choice of place of delivery Results: The study found that there was an association between socio-demographic factors and the influence on the choice of place of delivery. Socio-demographic predictors included Age, education, parity , marital status. Conclusion: The study demonstrates socio-demographic influence on the choice of place of delivery among mothers in the study area.
Keywords: Delivery; Maternity; Antenatal Care; Tassia kwa Ndege